2022
DOI: 10.1001/jama.2022.9805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pharmacogenomic Testing for Drug-Gene Interactions on Medication Selection and Remission of Symptoms in Major Depressive Disorder

Abstract: Key PointsQuestionDoes provision of pharmacogenomic testing for drug-gene interactions affect selection of antidepressant medication and response of depressive symptoms in patients with major depressive disorder (MDD)?FindingsIn this randomized clinical trial that included 1944 patients with MDD, provision of pharmacogenomic tests for drug interactions compared with usual care resulted in prescriptions with no predicted drug-gene interactions in 45% vs 18%, respectively, a difference that was statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 24 publications
0
57
0
Order By: Relevance
“…In research settings, genetics has also been shown to help identify prognostic factors, although their clinical applicability has remained unresolved so far [ 35 ]. Furthermore, genetic variation in drug response (pharmacogenomics) has been widely investigated: while evidence supports lower chances of drug-gene interactions for patients undergoing pharmacogenetic testing, effects of such genetic testing on remission rates have remained unclear [ 36 ]. In line with such findings, the CPIC has issued guidelines on the dosing of antidepressants according to CYP2C19 and CYP2D6 genotypes [ 37 , 38 ].…”
Section: Potential Of Genetic Testing In Clinical Settingsmentioning
confidence: 99%
“…In research settings, genetics has also been shown to help identify prognostic factors, although their clinical applicability has remained unresolved so far [ 35 ]. Furthermore, genetic variation in drug response (pharmacogenomics) has been widely investigated: while evidence supports lower chances of drug-gene interactions for patients undergoing pharmacogenetic testing, effects of such genetic testing on remission rates have remained unclear [ 36 ]. In line with such findings, the CPIC has issued guidelines on the dosing of antidepressants according to CYP2C19 and CYP2D6 genotypes [ 37 , 38 ].…”
Section: Potential Of Genetic Testing In Clinical Settingsmentioning
confidence: 99%
“…Precision medicine approaches involving pharmacogenomic testing for drug-gene interactions do indeed reduce prescription of medications with predicted drug-gene interactions. However, effects on patient outcomes such as symptom remission are small and short-lived [23].…”
Section: Text Box 3: Spectrum Biasmentioning
confidence: 99%
“…Their influence on hospitalization needs to be analyzed in the future to gain more understanding of the role of all genes on efficacy and adverse drug reactions to psychotropic drugs. Results from the PRIME Trial (pharmacogenes only) in comparison to the GUIDED Trial (pharmacodynamic and pharmacokinetic genes) are not differing substantially in remission and response rates in patients with major depressive disorder, questioning the impacts of pharmacodynamic genes on patient outcomes [ 53 , 54 ]. The “uncommon” metabolism profile is very common as 100% of our cohort had divergent genotypes.…”
Section: Limitationsmentioning
confidence: 99%
“…As the role of clinical pharmacists is evolving, collaborative care models, including clinical pharmacists’ services (available in the U.S. and Germany) are needed [ 56 ]. Ignoring the scientific evidence on the influence of genetic polymorphism on the pharmacokinetics of antidepressants and antipsychotics put patients at risk of adverse drug reactions or inefficacy of the drugs that might lead to chronicity of the disease and/or admission to a psychiatric hospital [ 53 ]. Further, pharmacogenes are important for 70–80% of all clinically used drugs and therefore PGx plays an important role in all patients who require a drug therapy, regardless of ethnicity [ 57 ].…”
Section: Limitationsmentioning
confidence: 99%